Upshots of second stage lower segment caesarean section - Reddy P., Mounica; Vellanki, Janaki (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Second stage caesarean section is done at full dilatation of cervix with head deeply engaged in the pelvis. Indicated in dystocias, unsuccessful trial of instrumental deliveries, non-reassuring fetal CTG, second stage arrest, deep transverse arrest. This study aimed to evaluate the indications, intraoperative and postoperative complications and fetomaternal outcome in second stage lower segment caesarean section (LSCS). Methods: This was a retrospective study conducted at Gandhi Medical College, Secunderabad from August 2022 to 2023. Results: Total 180 cases underwent second stage LSCS during this period. Among them majority of the age group belonged to 26-30 years (37.8%), unbooked cases (88.9%) and primi gravida (73.3%). Most common indications were cephalopelvic disproportion (38.8%) and fetal distress (14.6%). The commonly used method was Patwardhan method 33.3% followed by vertex 37.7%. The common complications were PPH (55.8%) and extension of incision site (16.7%). Fetal complications were birth asphyxia (45%), mortality (10%). Postoperative complications were febrile illness (16.1%), prolonged stay (35%) and anemia (20%). Conclusions: A proper judgement and skilled obstetricians are required to perform a second stage LSCS.